Primary Congenital Glaucoma with Delayed Suprachoroidal Hemorrhage following Combined Trabeculotomy Trabeculectomy and 5-Fluorouracil - Roseline Duke; Anthonia Ikpeme (Case Reports in Ophthalmological Medicine)
Background. Delayed postoperative suprachoroidal hemorrhage (DSCH) may occur following intraocular surgery for the treatment of glaucoma. It is considered to be a rare and debilitating event if not managed appropriately. Reported herewith is a case of Primary Congenital Glaucoma followed by DSCH with successful immediate surgical intervention and visual restoration. Patient and Method. An 8-month-old male child had bilateral Primary Congenital Glaucoma (PCG). Combined Trabeculotomy Trabeculectomy with 5-Fluorouracil (5FU) was performed. He developed delayed suprachoroidal hemorrhage (DSCH) within 24 hours after intraocular surgery which was drained. In addition, he developed exposure keratopathy and left amblyopia. Outcome. Resolution of the DSCH was seen with surgical drainage in addition to treatments for exposure keratopathy and amblyopia. These resulted in reduced intraocular pressure and improved visual acuities. Conclusion. There appears to be a difference in the overall management of PCG and DSCH between adults and children. A high index of suspicion as well as emergency surgical treatment for DSCH and associated conditions should be performed on pediatric patients that present with these challenges.